2022
DOI: 10.3390/cells11040601
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Sialylation Status and Cell Susceptibility to Amyloid Toxicity

Abstract: The interaction between the cell membrane and misfolded protein species plays a crucial role in the development of neurodegeneration. This study was designed to clarify the relationship between plasma membrane composition in terms of the differently linked sialic acid (Sia) content and cell susceptibility to toxic and misfolded Aβ-42 peptides. The sialylation status in different cell lines was investigated by lectin histochemistry and confocal immunofluorescence and then correlated with the different propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…It's also been shown that cell lines with high levels of SA are more vulnerable to Aβ toxicity. This toxicity may cause a change in neuron metabolism, resulting in a reparative rise in SA, which may favor amyloid binding to GM1, aggravating cell dysmetabolism and promoting more amyloid aggregation (Bucciantini et al, 2012; Sgambati et al, 2022a). Being a chief ligand for microglial Siglecs, an immunoglobulin‐type lectins (sialoadhesin), it holds a critical role in microglial homeostasis in the healthy brain (Li et al, 2021; Rawal & Zhao, 2021; Sundaram, 2017; Tosi et al, 2010; Wo et al, 2017; Xu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It's also been shown that cell lines with high levels of SA are more vulnerable to Aβ toxicity. This toxicity may cause a change in neuron metabolism, resulting in a reparative rise in SA, which may favor amyloid binding to GM1, aggravating cell dysmetabolism and promoting more amyloid aggregation (Bucciantini et al, 2012; Sgambati et al, 2022a). Being a chief ligand for microglial Siglecs, an immunoglobulin‐type lectins (sialoadhesin), it holds a critical role in microglial homeostasis in the healthy brain (Li et al, 2021; Rawal & Zhao, 2021; Sundaram, 2017; Tosi et al, 2010; Wo et al, 2017; Xu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…SA levels are found highest in brain endothelial cells where it functions as an important regulator of neurogenesis, neuronal repair and remodeling. SA is a possible contender for inhibiting Aβ aggregation and decreasing neuroinflammatory responses through sialylation, which improves Aβ interaction, cellular internalization, and transport through the brain by endorsing their binding with the GM1 ganglioside receptor (Bucciantini et al, 2012; Gallart‐Palau et al, 2021; Sgambati et al, 2022a; 2022b; Sundaram, 2017). AA was also found to be the most effective (97%) and potent against Aβ neurotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Various amyloids can distinctively affect different cell types, with the effects of fibrils specifically linked to their interaction with plasma membrane ligands and binding to lipid-rafts on the cell surface . For example, a significant inverse relation was observed between the membrane cholesterol content and the cellular damage inflicted by amyloids, and cells with a neuron-like phenotype and high levels of sialic acid in the cell membrane were particularly susceptible to amyloids such as Aβ . Thus, different cell types manifesting varying compositions and levels of plasma membrane receptors and displaying different surface properties can alter susceptibility to amyloids.…”
Section: Discussionmentioning
confidence: 99%